Assessing the efficiency of China's environmental regulation on carbon emissions based on Tapio decoupling models and GMM models - Wenbo Guo; Yan Chen (Energy Reports, 2018)
This paper takes 30 provinces in China from 2004 to 2015 as research samples, using the Tapio decoupling models, differential GMM methods and peak forecasting models to analyze the effect of environmental regulation on carbon emissions, and subdividing the research sample from the regional and temporal dimensions to analyze the effectiveness of environmental regulations in different regions and at different time periods. The analysis results show that, with the advancement of environmental regulation, the dependence of China's economic growth on fossil energy has experienced a process from weak to strong and weak. There is a significant inverted U-shaped curve relationship between environmental regulation and CO2 emissions and CO2 emissions intensity. As the intensity of environmental regulation changes from weak to strong, the impact effect changes from "green paradox" effect to "back-forced reduction" effect. The effect of environmental regulation in the eastern region is better than that in the central and western regions. However, with the implementation of environmental regulation, the inverted U-shaped curve between environmental regulation and carbon emissions gradually becomes flat. The results of the peak forecast show that China has crossed the peak of CO2 emissions intensity, but has not exceeded the peak of CO2 emissions. By further optimizing environmental regulations, China may reach its CO2 emissions peak by 2030. Overall, China's environmental regulations at the current stage can effectively curb carbon emissions and achieve the desired goals.
Keywords: 330; Carbon emissions; Differential GMM method; Environmental regulation; Tapio decoupling model